2006
DOI: 10.1099/vir.0.82388-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the first American bottlenose dolphin papillomavirus: Tursiops truncatus papillomavirus type 2

Abstract: A novel papillomavirus (PV) was isolated from a genital condyloma of a free-ranging bottlenose dolphin inhabiting the coastal waters of Charleston Harbor, SC, USA: Tursiops truncatus papillomavirus type 2 (TtPV2). This novel virus represents the first isolated North American cetacean PV and the first American bottlenose dolphin PV. After the viral genome was cloned, sequenced and characterized genetically, phylogenetic analyses revealed that TtPV2 is most similar to the only published cetacean PV isolated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 51 publications
0
46
1
1
Order By: Relevance
“…Although papillomavirus has been associated with genital lesions in bottlenose dolphins (Rehtanz et al, 2006), we found no evidence of papillomavirus infection in these genital mucosa lesions. Papillomavirus DNA was not detectable by PCR in any of the samples of the genital mucosa or in the biopsied material from the penile lesion of dolphin 19.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Although papillomavirus has been associated with genital lesions in bottlenose dolphins (Rehtanz et al, 2006), we found no evidence of papillomavirus infection in these genital mucosa lesions. Papillomavirus DNA was not detectable by PCR in any of the samples of the genital mucosa or in the biopsied material from the penile lesion of dolphin 19.…”
Section: Discussioncontrasting
confidence: 44%
“…Because papillomavirus is known to cause genital lesions in bottlenose dolphins (Rehtanz et al, 2006), a papillomavirus PCR was performed on all genital mucosa samples collected in lysis buffer using primers MY11/ MY09 (Manos et al, 1989) and GP5 Roda Husman et al, 1995). This PCR had been successful in detecting DNA of two Phocoena spinnipensis papillomaviruses, one of which is closely related to bottlenose dolphin papillomavirus 2 (Van Bressem et al, 2007).…”
Section: Papillomavirus Pcrmentioning
confidence: 99%
“…coelebs and Fringilla montifringilla. 31 To date, there have been no reports of papillomaviruses or any neoplastic lesions in free-ranging seabirds despite the identification of papillomaviruses in numerous marine mammals, 5,35 including dolphins, 36,37 porpoises, 43 and sea turtles. 18 Regardless of host species, productive papillomavirus infection (formation of infectious particles) has been invariably tied to the terminal differentiation of epithelial cells.…”
mentioning
confidence: 99%
“…Immunostaining of recombinant baculovirus-infected cells indicated a high level of expression of L1 protein with a homogenous nuclear distribution (data not shown). The recombinant TmPV1 L1 protein showed the ability to self-assemble into empty VLPs, as reported for L1 of all other PVs expressed using a baculovirus system (Kirnbauer et al, 1993;Rose et al, 1993;Rehtanz et al, 2008). Purified VLPs were approximately 55 nm in diameter and had the morphologic appearance of icosahedral particles (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The TmPV-VLPs are the optimal reagent to measure anti-TmPV1 antibodies resulting from both previous and current infections, whereas DNA detection only reflects the current status (Marais et al, 2000;Stone et al, 2002). In the past, VLP-based ELISAs were successfully used to evaluate PV antibody prevalence in other marine mammal species (Rehtanz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%